Leadership in Action: Exploring Teacher Perceptions of Elementary School Principals in Rural Contexts - Fitri Yulianti; Azizatul Khairi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Effective principal leadership is critical for educational quality, yet empirical research on elementary school leadership in rural Indonesian contexts remains limited. This study examines teacher perceptions of principal leadership effectiveness across three core dimensions: personality traits, task implementation, and social relationship capabilities. The research was conducted in Nibung District, Musi Rawas Utara Regency, a rural area with diverse educational characteristics. A quantitative descriptive approach was employed, surveying 60 teachers selected through proportional random sampling from 238 elementary school teachers. Data were collected using validated questionnaires demonstrating strong psychometric properties (Cronbach's α = 0.832-0.856; CVI = 0.89) and analyzed using percentage techniques. Results indicate consistently positive teacher perceptions across all dimensions: personality (84%), task implementation (81.5%), and social capabilities (82.5%). Principals demonstrated particular strengths in providing responsible autonomy, modeling accountability, and building collaborative environments. However, areas requiring enhancement were identified in readiness planning, goal achievement encouragement, and conflict management capabilities. This study makes significant contributions to educational leadership literature by providing an integrated multidimensional analysis of principal competencies within rural Indonesian contexts—an understudied area in Southeast Asian educational research. The novelty lies in examining the intersection of teacher perceptions, leadership competency dimensions, and rural contextual factors. Findings provide empirical foundations for policy development and targeted professional development programs, particularly addressing strategic planning, motivational coaching, and conflict resolution competencies essential for sustainable elementary school improvement in resource-constrained rural settings.